MALT1-Dependent Cleavage of HOIL1 Modulates Canonical NF-κB Signaling and Inflammatory Responsiveness - Fung, Shan-Yu; Lu, Henry Y.; Sharma, Mehul; Sharma, Ashish A.; Saferali, Aabida; Jia, Alicia; Abraham, Libin; Klein, Theo; Gold, Michael R.; Noterangelo, Luigi D.; Overall, Christopher M.; Turvey, Stuart E. (Frontiers in Immunology, 2021)
Nuclear factor kappa B (NF-B) is a critical transcription factor involved in regulating cell activation, inflammation, and survival. The linear ubiquitin chain assembly complex (LUBAC) which consists of HOIL1, HOIP, and SHARPIN, catalyzes the linear ubiquitination of target proteins—a post-translational modification that is essential for NF-B activation. Human germline pathogenic variants that dysregulate linear ubiquitination and NF-B signaling are associated with immunodeficiency and/or autoinflammation including dermatitis, recurrent fevers, systemic inflammation and enteropathy. We previously identified MALT1 paracaspase as a novel negative regulator of LUBAC by proteolytic cleavage of HOIL1. To directly investigate the impact of HOIL1 cleavage activity on the inflammatory response, we employed a stable transduction system to express and directly compare non-cleavable HOIL1 with wild-type HOIL1 in primary HOIL1-deficient patient skin fibroblasts. We discovered that non-cleavable HOIL1 resulted in enhanced NF-B signaling in response to innate stimuli. Transcriptomics revealed enrichment of inflammation and proinflammatory cytokine-related pathways after stimulation. Multiplexed cytokine assays confirmed a ‘hyperinflammatory’ phenotype in these cells. This work highlights the physiological importance of MALT1-dependent cleavage and modulation of HOIL1 on NF-B signaling and inflammation, provides a mechanism for the autoinflammation observed in MALT1-deficient patients, and will inform the development of therapeutics that target MALT1 paracaspase and LUBAC function in treating autoinflammatory skin diseases.